Graphene mechanical pixels for Interferometric Modulator Displays. Issue 1 (December 2018) - Cartamil-Bueno, Santiago; Davidovikj, Dejan; Centeno, Alba; Zurutuza, Amaia; Zant, Herre; Steeneken, Peter; Houri, Samer
Abstract Electro-optic modulators based on micro-electromechanical systems have found success as elements for optical projectors, for simplified optical spectrometers, and as reflective-type screens that make use of light interference (Interferometric Modulator Display technology). The latter concept offers an exciting avenue for graphene nanomechanical structures to replace classical micro-electromechanical devices and bring about enhancement in performance, especially switching speed and voltage. In this work we study the optical response of electrically actuated graphene drumheads by means of spectrometric and stroboscopic experiments. The color reproducibility and speed of these membranes in producing the desired electro-optic modulation makes them suitable as pixels for high refresh rate displays. As a proof of concept, we demonstrate a Graphene Interferometric Modulator Display prototype with 5 μm-in-diameter pixels that compose a high resolution image (2500 pixels per inch)—equivalent to a 5″ display of 12K—whose color can be changed at frame rates of at least 400 Hz. The electro-optical response of suspended graphene membranes measured by change in wavelength-dependent reflectance can enable interferometric modulation display (IMOD) technology. Here, the authors report suspended double layer graphene based IMOD drums with 2500 pixels per inch.